Challenge to promote change: both young and older adults benefit from contextual interference - Pauwels, Lisa; Vancleef, Kathleen; Swinnen, Stephan P.; Beets, Iseult A. (Frontiers in Aging Neuroscience, 2015)
Current society has to deal with major challenges related to our constantly increasing population of older adults. Since motor performance generally deteriorates at older age, research investigating the effects of different types of training on motor improvement is particularly important. Here, we tested the effects of contextual interference (CI) while learning a bimanual coordination task in both young and older subjects. Both age groups acquired a low and high complexity task variant following either a blocked or random practice schedule. Typical CI effects, i.e. better overall performance during acquisition but detrimental effects during retention for the blocked compared with the random groups, were found for the low complexity task variant in both age groups. With respect to the high complexity task variant, no retention differences between both practice schedules were found. However, following random practice, better skill persistence (i.e. from end of acquisition to retention) over a one week time interval was observed for both task complexity variants and in both age groups. The current study provides clear evidence that the effects of different practice schedules on learning a complex bimanual task are not modulated by age.